Optimalisasi Branding dan Pemasaran Digital pada Produk UMKM Lokal Desa Dolok Kahean - Dila Septiani; Salman Nasution (Lembaga Pengembangan Kinerja Dosen, 2025)
Optimizing Branding and Digital Marketing as an urgent solution for local MSMEs, particularly Rengginang producer Ibu Saliem in Dolok Kahean Village. This MSME was previously limited to traditional marketing, which hampered market expansion and competitiveness. This community service aims to transform this local business to be competitive in the digital era. The method used is descriptive qualitative with stages of observation, socialization, and program implementation. The main intervention includes the creation of the Rengginang Huta brand identity with a professional logo design. This new logo combines elements of the business's heritage since 1989 and integrated contact information, which strategically increases the selling value and credibility of the product. The second pillar is the implementation of Digital Marketing through the creation of the Instagram account @rengginanghuta_ibusaliem. This account serves as a virtual storefront to overcome geographical limitations and increase reach to a wider consumer base. Intensive training was also provided on content strategies that focus on credibility, sales (Call to Action), and interaction. The results of this community service confirm that the integration of strong and authentic branding with digital marketing strategies is a key catalyst for MSMEs to transform and increase sales turnover. The next challenge lies in the sustainability of content strategies and independent account management by MSMEs to achieve optimal economic potential for Dolok Kahean Village.